Application of spartial interpolation method in synthesis of video sequence intermediate frames - Nemcev, N.S.; Gilmutdinov, M.R.; Veselov, A.I. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2018)
Subject of Research.We have carried out the research of existing synthesis methods of the video sequence intermediate frames based on the procedure of motion estimation and compensation. A method for the video sequence intermediate frames synthesis is proposed based on the techniques of images spatial interpolation and the procedure for true motion estimation and compensation of the video sequence. Method. The paper describes the approach for the synthesis of video sequence intermediate frames based on the true motion estimation principle. The approach is based on the iterative hierarchical refinement procedure for the elements of the vector field and the approach for spatial interpolation of particular regions of the frame based on the image area fill techniques. Main Results. Сomparison results of the proposed approach with existing modern analogs show its higher efficiency in synthesizing frames of video sequences containing objects with complex motion. Practical Relevance. The proposed approach can be used in practice in the task of video sequences encoding and increasing of their frame rate